Barrier in understanding defect liability period from homeowner’s perspectives / Nor Aina Roshisan and Mohd Nurfaisal Baharuddin - Roshisan, Nor Aina; Baharuddin, Mohd Nurfaisal (2023)
This paper examines the defect liability period in homeownership, where homeowners rely on builders and contractors to address post-construction flaws. It focuses on homeowner perspectives, including their concerns, rights, and obligations during this period. Common challenges faced by homeowners include a lack of knowledge about the defect liability period and consistent reports of defects in newly built houses. The research aims to identify barriers to understanding the defect liability period from homeowners' perspectives and propose effective solutions. A questionnaire was used to gather opinions on nine factors related to homeowner understanding of this period. Recommendations based on most respondents’ opinions include developing guidelines, improving communication, providing clear explanations in agreements, and ensuring transparency. Implementing these recommendations can enhance homeowner understanding, resulting in smoother defect resolutions and improved homeowner experiences.